2014
DOI: 10.1186/1746-160x-10-28
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective study of biopsied head and neck lesions in a cohort of referral Taiwanese patients

Abstract: IntroductionA study of the whole spectrum of biopsied head and neck (HN) diseases in Taiwan has not yet been performed. Therefore, the current study aimed to provide updated information about HN lesions in a cohort of referral Taiwanese patients for histopathological examination.MethodsHN lesions (2000–2011) in patients with records of age, sex, and histological diagnoses were retrieved from the Oral Pathology Department of the institution. These lesions were classified into four main categories: tumor/tumor-l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

19
23
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(46 citation statements)
references
References 39 publications
19
23
4
Order By: Relevance
“…11 Our research study showed a preponderance of males in all three histopathological categories which was in accord with the findings of Siddiqui M S et al 15 A wide variety of lesions spanned across the seven topographic sites we analyzed. Lesions arising from the skin and the soft tissues were found to be maximum (29.65%) in present study.…”
Section: Discussionsupporting
confidence: 79%
See 4 more Smart Citations
“…11 Our research study showed a preponderance of males in all three histopathological categories which was in accord with the findings of Siddiqui M S et al 15 A wide variety of lesions spanned across the seven topographic sites we analyzed. Lesions arising from the skin and the soft tissues were found to be maximum (29.65%) in present study.…”
Section: Discussionsupporting
confidence: 79%
“…In a study by Kanu OO et al, more number of benign cases (63.3%) were reported which was compatible with our study. 3 However, least number of benign lesions were noted in the study by Lei F et al 11 The benign lesions were more frequent in the age group of 20 to 50 years while higher percentage of malignant lesions belonged to age group of 51years and above in our research work. These observations were in agreement with the findings of Popat V et al 5 Inflammatory lesions were maximum in the younger age of 20 years and below in our analysis.…”
Section: Discussioncontrasting
confidence: 37%
See 3 more Smart Citations